Synthesis of carbon nanotube/titanate nanotube composites with photocatalytic activity for H2S oxidation. (4th May 2017) - Vu, Thu Ha Thi; Au, Hang Thi; Nguyen, Thu Trang Thi; Do, Manh Hung; Pham, Minh Tu; Bui, Duy Hung; Phan, Thanh Son; Nguyen, Dinh Lam
ABSTRACT: Composites of carbon nanotubes – titanate nanotubes (MWNTs/ TNTs) – were successfully synthesized by the hydrothermal reaction process. The morphology of the MWNTs/TNTs composites was observed by transmission electron microscopy. Fourier transform infrared spectroscopy was used to characterize the molecular interactions between TNTs and MWNTs in the composites. The X-ray diffraction of TNTs and MWNTs/TNTs composites exhibited the existence of titanate phase (100), (102), (020) and (422). The charge recombination of MWNTs/TNTs composites was examined by photoluminescence spectrum. The photocatalytic activity of TNTs and MWNTs/TNTs composites was evaluated on the basis of the model oxidation reaction of H2 S. GRAPHICAL ABSTRACT: